The Role Of Microcredit Financing On Women Empowerment In Malaysia - Al-Shami, Samer Ali (UTeM, 2016)
Microcredit has become a buzzword in the credit markets as an effective tool to deliver financial services to deprived women in the absence of conventional credit markets. The underlying logic is that through extending microcredit, women will be able to participate in economic market through forming their micro and small businesses. Consequently, they will gain incomes and contribute to their household supports to reduce their vulnerability and empower them. Although microfinance has reached the peak of momentum, recent literature documented conflicting evidence and demonstrated that empowerment may not or may only be partially achieved, especially in the Muslim community. Therefore, this study examines the effect of microcredit on Malay Muslim women empowerment in urban Selangor and Melaka. An explanatory mixed method was employed for the study. In the first step, a cross-sectional survey was distributed to 500 respondents to examine the effect of microfinance on women livelihood and decision-making process in intra-household as well as business. A multi-stage random sampling was used to collect data from urban areas in Selangor and Melaka. The time of joining AIM scheme was used to determine the type of treatment and control members, where 360 of current clients who spent three years in the AIM scheme are referred to as the treatment group and 140 of new clients who just joined the AIM scheme and have not yet used their loans are referred to as the control group. In the second step, 32 semi structured interviews were performed to deeply explain how access to AIM affects women empowerment. The logistic regression result shows that AIM has positive effect on women livelihood and decision-making process and resources controlling in intra-household as well as business. The finding of qualitative content analysis also confirms the impact of AIM on women empowerment. It also explains how access to microfinance shifts the strategy of decision-making process from solely husband or family base to self or jointly decision-making base. Moreover, the content analysis results show how access to microfinance empowers women in their community. Despite the significant impact of AIM on women empowerment, there are internal as well as external challenges faced by women borrowers which impede their sustainability and growth that need to be addressed by future researches. Therefore, this research recommends the policymakers to continue support poor and low income women and protect their micro and small businesses from massive competition and market monopoly as well as diversify their product and redesign microcredit disbursement and repayment process